Determinant Factor Affecting Impulsive Buying Behavior of Fashion Products in E-Commerce - Fedianty Augustinah; Christina Yanita Setyawati; Acai Sudirman (LPPM Universitas Terbuka, 2023)
Purpose – This research aimed to analyze determinant factors influencing impulsive buying behavior of fashion products in E-Commerce. Methodology – Research instruments and quantitative data analysis were adopted for predetermined testing. The data was gathered using documentation instruments and the distribution of online questionnaires. The foundation for selecting the sample was oriented towards a non-probability sampling method using a purposive sampling formula. This research comprised a sample of 200 consumers who made buying of fashion products through E-Commerce. Findings – The results showed that celebrity endorser, fashion involvement, and shopping lifestyle positively and significantly affected impulsive buying. Meanwhile, sales promotion had a positive and insignificant effect on impulsive buying. Originality – The interaction between shopping lifestyle and fashion involvement formed very high impulsive buying patterns on E-Commerce. These two concepts were interrelated and strengthened each other. Consumers with a shopping lifestyle driven by high fashion involvement might be prone to impulsive buying, specifically when there was a stimulus related to fashion preferences and trends.